The Ability of Fibrinogens, FI and FII, to Support ADP- Induced Platelet Aggregation - Phillips, H M; Mansouri, A; Perry, C A (Thrombosis and Haemostasis, 1983)
Fibrinogen plays an integral part in ADP-induced platelet aggregation. Controversy exists in regard to the role of the carboxy termini of fibrinogen Aa chains in this reaction. We have attempted to clarify this problem in view of the availability of a highly purified FII fibrinogen fraction. Kabi fibrinogen or its purified fractions FI, FII and FIII-IV-V were added to washed platelets in the presence of Tyrode-HEPES buffer pH 7.4. Aggregation was initiated by the addition of calcium and ADP. These fibrinogen fractions equally promoted ADP-induced platelet aggregation. The major difference among these fractions is in their Aα chains. The FI fraction contains intact Aα chains while FII and FIH-IV-V fractions have one and two partially degraded Aα chains at the carboxy terminal portion respectively. We conclude that the carboxy terminal portion of the Aα chain does not play an important role in promoting ADP-induced platelet aggregation.
Keywords: Fibrinogen; Platelet aggregation; Fibrinogen fractions